Hubungan Sikap Ibu dengan Perilaku Pemberian Makan pada Anak Toddler - Munte, Mei Indah; Ganis Indriati; Yufitriana Amir (POLTEKKES KEMENKES YOGYAKARTA, 2022)
Proper feeding of toddlers is very important in the process of child growth and development, feeding can be influenced by the mother's attitude and behavior. The purpose of this study was to determine the relationship between the mother's attitude and the behavior of feeding children toddler in Puskesmas Rejosari, Pekanbaru. This study uses a quantitative method, the type of correlational research with aapproach cross sectional. Samples is 89 mothers with toddler in accordance with the inclusion criteria using a formula slovin. The analysis used is bivariate analysis using Chi-square test. The results showed that 89 respondents who were studied showed that the highest maternal age group was 26-35 (58.4%), the majority of the education level were SMA (60.7%), most of the mothers were IRT (75.3%). Attitudes of mothers who have a negative attitude and have good behavior in feeding there are 21 mothers (51.2%), while mothers who have a positive attitude have good behavior in feeding totaling 30 respondents (62.5). Statistical analysis showed no significant relationship between maternal attitudes with behavior in child feeding toddler with a p-value = 0.391 with an alpha of 0.05, so that the p-value> alpha (0:05). There is a weak relationship between the mother's attitude and the behavior of feeding children toddler in Puskesmas Rejosari, Pekanbaru. Results Based on the research obtained, these variables in the same direction means the positive attitude of the mother, the mother likely to have a good behavior in feeding toddler. Keywords : Attitude, behavior, feeding